Cannibal Holocaust. (1st August 2013) - Foss, Paul
A Fire In My Belly (1986-87) and Cannibal Holocaust (1980) are more alike than you think. The former is a silent black-and-white short film by New York artist David Wojnarowicz, who died of AIDS complications in 1992. What emerges from its disjointed montage sequences are traces of religious and various other totems and taboos, adding up to a grim picture of a barbaric society.